¿Cuál es mi país? Alteridad e Identificación en el ámbito escolar - Bravo Torres, Carmen Clara (Comparative Cultural Studies: European and Latin American Perspectives, 2018)
This paper analyzes how from the country of origin, teachers of standard classrooms denominate to students of foreign nationality as different and the identification of these young people with the category mentioned. For it, we will be referring to students who have remained in Temporary Classrooms Linguistic Adaptation (Andalucía, Spain).Teaching staff point out that depending on the country of origin, these students will have different motivations, certain future expectations and a family-school relationship that does not always fit the reality. However, thanks to the students’ speech, you can see that this is not always the case. From the young people’s speech, we perceive how they do not feel identified with such a category. They feel identified like the rest of the young Spaniards. However, they are aware that students of foreign nationality are perceived differently than those considered Spanish. In order to carry out this work, the studies already carried out on this topic and the speeches used by the different subjects have been of great importance. Therefore, this research has been based on an ethnography will be carried out by bibliographical review, participant observation, discussion groups and different interviews. Thus, this paper will be realized from these techniques and the objectives set forth; where otherness and identification will be key to its development.